Stable isotope data from the Gomez ice core (GZ07), Bryan Coast, South-Western Antarctic Peninsula - Thomas, Elizabeth (Polar Data Centre; British Antarctic Survey, Natural Environment Research Council; Cambridge, CB3 0ET, UK., 2017)
This dataset provides an annual isotope record from the Gomez (GZ07) ice core, dating back to the 1850s. The 136 m core was drilled on the South-western Antarctic Peninsula, during January 2007. We present a new 150-year, high-resolution, stable isotope record (δ18O) from the Gomez ice core, drilled on the data sparse south western Antarctic Peninsula. The record is highly correlated with satellite-derived temperature reconstructions and instrumental records from Faraday station on the north west coast, thus making it a robust proxy for local and regional temperatures since the 1850s.